Dipole Types of Autumn Precipitation Variability Over the Subtropical East Asia‐Western Pacific Modulated by Shifting ENSO. Issue 17 (6th September 2018) - Hu, Chundi; Chen, Dake; Huang, Gang; Yang, Song
Abstract: Recent autumns have exhibited two dipole types of precipitation variability (DIPO1 and DIPO2) over the subtropical East Asia‐western Pacific (SEAWP). Meanwhile, El Niño–Southern Oscillation (ENSO) has undergone significant mode shift, exhibiting as the eastern Pacific or central Pacific ENSO (EPSO or CPSO). Whether there was any physical linkage between the two remains unclear. Here we demonstrate for the first time that interannual variations of DIPO1 and DIPO2 are closely linked to EPSO and CPSO, respectively. Shifting ENSO modulates the patterns of SEAWP precipitation dipole mainly via changing the path of tropospheric moisture transport and the location of anomalous water vapor convergence/divergence due to different low‐level cyclone/anticyclone activities induced by EPSO or CPSO. Further analysis shows that the interdecadal variability of SEAWP precipitation is also linked to the La Niña‐like climate shift in 1998. Hence, our study provides some new insight into the ongoing hot debate on the shifting ENSO and increasing autumn drought in southeastern China. Plain Language Summary: We explore the mode changes in the subtropical East Asia‐western Pacific (SEAWP) precipitation variability during boreal autumn over 1979–2016, which is important for crop ripening and harvest from the autumn drought perspective. Results show that the eastern Pacific ENSO (El Niño–Southern Oscillation) and central Pacific ENSO primarily drive the DIPO1 and DIPO2 via modifying the low‐level atmospheric circulation and moisture response over the SEAWP, respectively. So it should be emphasized that shifting ENSO is responsible for modulating the SEAWP precipitation dipoles to certain extent in the context of global warming. Key Points: Two different dipole types of autumn precipitation variability are found in the SEAWP during the satellite era Changes in the dipole‐type precipitation anomaly are linked to shifting ENSO Shifting ENSO modulates SEAWP precipitation dipoles mainly via different low‐level circulations and the resultant water vapor activities